WASTE BANK CONCEPT: Having Savings and Income from Waste - Nugroho, Alan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
The rise of the concept of a waste bank in Indonesian society has its own charm, for example about savings and income from waste. The reason is, so far waste has no value, and even tends to be a problem for the environment. The presence of the waste bank concept is a breath of fresh air that can minimize the risk of waste problems, as well as provide economic benefits. This study was conducted to analyze waste bank activities that generate economic benefits, through the concept of waste bank savings. This research was conducted at the waste bank group in Pondok Pinang sub-district, Jakarta. The research correspondents were members of the waste bank, as many as 54 people. The research method uses quantitative techniques with regression analysis. Research data obtained through the distribution of questionnaires. The results of the study confirm that the waste bank activity is considered positive, because it is an alternative to solving the waste problem and also provides material benefits, although it is acknowledged by the community that it is not significant. However, the proceeds from savings from waste bank activities are quite beneficial for funding community activities. Statistically, the number of waste bank activities can increase savings, and have implications for increasing waste bank income.